2022
DOI: 10.19080/jojms.2022.07.555708
|View full text |Cite
|
Sign up to set email alerts
|

The Morphological Properties of Zns Nanoparticles Deposited on Glass Substrates as a Function of Aluminum Content

Abstract: The pulsed-laser deposition (PLD) method was used to deposit undoped zinc sulphide (ZnS) and Al-doped zinc sulphide (AZS) films on glass substrates (GSs). The aluminum content in the ZnS films varied from 0% to 8%. The film morphology was studied using atomic force microscopy (AFM). The films were optically characterized using an Ultraviolet-Visible-near-infrared (UV-VIS-NIR) spectrophotometer with photon wavelengths ranging from 300 to 600nm. The average roughness (Sa), root-mean square (RMS) roughness (Sq), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Mashair [18] used Maxwell's equations to prove theoretically the expression of frequency-dependent absorption coe cient. In Ahmed and Eisa [19,20,21] thin lms the absorption coe cient is frequency dependent. The study of Gregory and Louise [22,23] on some materials showed that the absorption coe cient decreased upon increasing the frequency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mashair [18] used Maxwell's equations to prove theoretically the expression of frequency-dependent absorption coe cient. In Ahmed and Eisa [19,20,21] thin lms the absorption coe cient is frequency dependent. The study of Gregory and Louise [22,23] on some materials showed that the absorption coe cient decreased upon increasing the frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed and Eisa [19,20,21] fabricated thin lms in which the absorption coe cient is frequency dependent. This means that they can act as nano-inductors or nanoelectronics capacitors.…”
Section: Introductionmentioning
confidence: 99%